IDEOLOGI PENDIDIKAN SYARIKAT ISLAM - Zainal Arifin Hoesein (VERITAS, 2017)
The essence of the organization of education is the intellectual counterpart towardschange. The value or quality of the desired change depends on the extent to which theactors of the change are directly involved and have the sincerity to change. Becausethe task of education is to develop the human nature to become a superior humanbeing, and able to create and develop a culture of high value and useful, so in itself theactors in the education process must have strategies and policies in building asupportive environment for the development of educational goals. In this perspective,every institution of education providers should be able to provide a direction ofeducational development that is conducive to the development of educational activities,including: the development of teaching-learning orientation, improvement of learningfacilities, the development of study networks, and self-discipline training.